Challenging the Morals of Western Society: The Use of Ritualized Sex in Contemporary Occultism - Bogdan, Henrik (Pomegranate, 2007)
This paper discusses the historical roots of the use of ritualized sex in contemporary occultism, with special focus on the teachings of Aleister Crowley (1875–1947), Gerald B. Gardner (1884–1964) and Kenneth Grant (b. 1924). The notion that sexual magic is related to Hindu Tantric practices is addressed, and a detailed historical development of the use of ritualized sex—as illustrated by Crowley, Gardner, and Grant—is presented.